Ethnobotanical survey and quantitative assessment of medicinal plants in landlocked communities of San Fernando, La Union, Philippines - Flores, Referenda Joanna V.; Cordero, Cecilia S.; Alejandro, Grecebio Jonathan D. (Frontiers in Pharmacology, 2025)
IntroductionKnowledge of medicinal plants is vital for preserving biodiversity, cultural heritage, and community healthcare. In San Fernando, La Union, traditional healing practices remain largely undocumented despite generational reliance on medicinal plants.MethodsThis study documented medicinal plants used in three landlocked barangays (Bacsil, Saoay, and Abut). Modified semi-structured interviews were conducted in October 2024 with 252 informants aged 20–88 years (10.6% of the total population), reaching data saturation at interview 215. Ethnobotanical indices, including Use Report (UR), Use Value (UV), Fidelity Level (FL), and Informant Consensus Factor (ICF), were calculated following established protocols to evaluate the cultural significance of plant species.ResultsA total of 93 plant species from 86 genera and 45 families were identified, treating 93 medical conditions across 17 disease categories. Fabaceae was the most represented family (11 species), followed by Lamiaceae and Poaceae (7 species each). Leaves were the most used plant part (62.3%), primarily prepared as decoctions (71.8%) for oral administration (68.4%). Vitex arvensis Gentallan, Sengun and M.B. Bartolome ranked highest across all ethnobotanical indices (UV = 1.54, RFC = 0.71, RI = 1.00), indicating broad medicinal applications and strong cultural recognition. Statistical analyses revealed significant geographic variation in knowledge (Kruskal-Wallis H = 45.23, p < .001): Barangay Saoay informants cited fewer species (5.2 ± 2.1) than Barangay Abut (8.4 ± 3.2; Mann-Whitney U, p < .001) and Bacsil (8.1 ± 2.9; Mann-Whitney U, p < .001). No significant differences were observed across gender (Mann-Whitney U, p = .909), civil status (Mann-Whitney U, p =.641), occupation (Kruskal-Wallis H, p = .564), education (Kruskal-Wallis H, p = .378), or age (Kruskal-Wallis H, p = .173).DiscussionThis research documents rich ethnobotanical knowledge in landlocked communities and demonstrates how geographic isolation influences knowledge distribution, providing quantitative foundations for conservation and future pharmacological investigations.